The year 2020, a milestone in breaking the vicious cycle of poverty and illness in China - Yun-Ping Wang; Xiao-Nong Zhou (BMC, 2020)
Abstract Marking the end of the five-year programme initiated by the Chinese Government to lift more than 70 million people out of poverty, the year 2020 is a milestone. Poverty alleviation has moved strongly forward in China and the major health indicators are now better than the average of all middle- and high-income countries. However, the dual burden of infectious and chronic diseases remains a challenge with respect to achieving the health target in the United Nations 2030 Agenda for sustainable development goals (SDGs). In 2015, about 44% of the poor population in China were impoverished by illness but already in 2018, multi-sectoral actions delivered by the Health-related Poverty Alleviation programme had reduced the number almost by half. In the past three years 15 million poor people (98% of the poor population) with infectious and chronic diseases had been treated and taken care of thanks to financial support through multiple health insurance schemes and other governmental subsidies. This article discusses the lessons learnt with regard to health-related poverty alleviation in China with special reference to those still remaining impoverished by illness. Consolidation of the achievements reached and provision of basic needs to those still disadvantaged and in poor health will require a major improvement of accessibility to, and affordability of, health services. The next step towards enhanced productivity and better living conditions will involve upgrading of the capacity of health professionals in the poor regions, promotion of coherent efforts in health-related poverty alleviation and rural revitalization measures. As an additional measure, data monitoring and research on health poverty alleviation should be strengthened as they are essential to generate the evidence and knowledge needed to support the move in the direction envisioned by the SDGs, and the new Healthy China 2030 programme.